Distinct transcriptomic signatures define febrile malaria depending on initial infective states, asymptomatic or uninfected - Kimenyi, KM; Akinyi, MY; Mwikali, K; Gilmore, T; Mwangi, S; Omer, E; Gichuki, B; Wambua, J; Njunge, J; Obiero, G; Bejon, P; Langhorne, J; et al. (BioMed Central, 2024)
Background: Cumulative malaria parasite exposure in endemic regions often results in the acquisition of partial immunity and asymptomatic infections. There is limited information on how host-parasite interactions mediate the maintenance of chronic symptomless infections that sustain malaria transmission. Methods: Here, we determined the gene expression profiles of the parasite population and the corresponding host peripheral blood mononuclear cells (PBMCs) from 21 children (< 15 years). We compared children who were defined as uninfected, asymptomatic and those with febrile malaria. Results: Children with asymptomatic infections had a parasite transcriptional profile characterized by a bias toward trophozoite stage (~ 12 h-post invasion) parasites and low parasite levels, while early ring stage parasites were characteristic of febrile malaria. The host response of asymptomatic children was characterized by downregulated transcription of genes associated with inflammatory responses, compared with children with febrile malaria,. Interestingly, the host responses during febrile infections that followed an asymptomatic infection featured stronger inflammatory responses, whereas the febrile host responses from previously uninfected children featured increased humoral immune responses. Conclusions: The priming effect of prior asymptomatic infection may explain the blunted acquisition of antibody responses seen to malaria antigens following natural exposure or vaccination in malaria endemic areas.